Studies on Characterisation of SBS Polymer Modified and Neat Bituminous Mixes Using Warm Mix Asphalt for Paving Applications - Anilkumar L.; Awanti S. S. (International Journal of Scientific Research in Civil Engineering, 2022)
With increasing concerns of global warming and increasing exhausation of gases, the asphalt industry looking for alternative for hot mix asphalt(HMA).warm mix asphalt(WMA) is a fast emerging new technology which has a potential of revolutionalizing the production of asphalt mixtures.WMA technology allows the mixing, lay down and compaction of asphalt mixes at significantly lower temperatures compared to hot mix asphalt(HMA). The technology can reduce production temperatures by as much as 30percent. Asphalt mixes are generally produced at 150°C or greater temperatures depending mainly on type of binder used.WMA mixes can be produced at temperatures of about 120°C or lower.In this study an attempt has been made to compare HMA(VG-30 and WMA (SBS-PMB40)with organic additives(Zycotherm ,Sasobit and Evotherm) with various dosages on Marshall properties for Dense Bituminous Macadam (DBM),Grade2.the adopted mixing temperatures for HMA was 155°C,130°C,and 120°C and mixing temperature for WMA was 130°C and 120°C.the laboratory study concludes that stability and Marshall properties for WMA mix were improved by addition of additives
Keywords: Wma; Hma; Sbs-Pmb-40; Vg-30; Sasobit; Evotherm; Asphalt Mixes; Marshall Properties